2019
DOI: 10.3892/mmr.2019.10478
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of expression profiles of long non‑coding RNAs with associated ceRNA�network involved in gastric cancer progression

Abstract: long non-coding rnas (lncrnas) play critical roles in the development and progression of cancers. The present study aimed to identify novel lncrnas and associated micrornas (mirnas or mirs) and mrnas in gastric cancer. differentially expressed lncrnas (delncrnas) and differentially expressed mrnas (demrnas) of 6 paired gastric cancer and normal tissues were identified using microarray. The demirnas between gastric cancer and the normal control tissues were identified using mirna-seq data from cancer Genome atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Construction of a ceRNA network contributes to reveal the occurrence and progression of cancer. Systematic analyses of ceRNA networks have been reported in lung cancer [ 28 ], gastric cancer [ 29 ], and colon cancer [ 30 ], but there have been few reports in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of a ceRNA network contributes to reveal the occurrence and progression of cancer. Systematic analyses of ceRNA networks have been reported in lung cancer [ 28 ], gastric cancer [ 29 ], and colon cancer [ 30 ], but there have been few reports in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs act as ceRNAs to regulate GC via the Wnt/β-catenin signaling pathway. Competing endogenous RNA (ceRNA) refers to a new mechanism of interaction between RNAs; that is, ceRNA binds to miRNA via microRNA response elements (MERs) to regulate target gene expression (47,48). A large number of studies have demonstrated that ceRNAs may be inextricably linked to multiple cancers, including GC (49)(50)(51).…”
Section: Lncrnasmentioning
confidence: 99%
“…It contains 4 exons and encodes 172 amino acids. MYL9 plays crucial function in various tumor progression and metastasis [6][7][8][9][10][11][12] . Recently, several reports show that MYL9 expression is different in various human tissues.…”
Section: Introductionmentioning
confidence: 99%